2018
DOI: 10.1016/j.ebiom.2018.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Early IL-10 producing B-cells and coinciding Th/Tr17 shifts during three year grass-pollen AIT

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 54 publications
5
72
0
3
Order By: Relevance
“…On the level of secreted factors, it was shown that cytokines such as Wnt5a (Wingless-Type MMTV Integration Site Family, Member 5a) or IL-24 are expressed as response to IL-4 stimulation only, while proteins with known pathological roles such as the IL-4 induced protein CCL-26 or periostin were shown to be upregulated by IL-4 and down-regulated in IFN-γ environment. These results were consistent when comparing upper and lower airway secretions, thus confirming nasal lining fluids as a proxy for the lower respiratory tract, particularly for epithelial type-2 biomarker like CCL-26 and IL24 (308,309). The E2-related transcription factor network contained the E2 hub-transcription factors GATA3, NFE2, MEIS1, HEY2, and AHR: GATA3 is well known as the master transcription factor of type-2 response in immune cells, however it was also shown to be expressed in airway epithelial cells.…”
Section: E2-polarized Airway Epitheliumsupporting
confidence: 70%
“…On the level of secreted factors, it was shown that cytokines such as Wnt5a (Wingless-Type MMTV Integration Site Family, Member 5a) or IL-24 are expressed as response to IL-4 stimulation only, while proteins with known pathological roles such as the IL-4 induced protein CCL-26 or periostin were shown to be upregulated by IL-4 and down-regulated in IFN-γ environment. These results were consistent when comparing upper and lower airway secretions, thus confirming nasal lining fluids as a proxy for the lower respiratory tract, particularly for epithelial type-2 biomarker like CCL-26 and IL24 (308,309). The E2-related transcription factor network contained the E2 hub-transcription factors GATA3, NFE2, MEIS1, HEY2, and AHR: GATA3 is well known as the master transcription factor of type-2 response in immune cells, however it was also shown to be expressed in airway epithelial cells.…”
Section: E2-polarized Airway Epitheliumsupporting
confidence: 70%
“…It appears that changes in the B‐cell compartment are quite restricted, as despite early reports of more global changes involving transitional and naive mature B cells in atopic dermatitis, these could not be replicated, and do not appear to be affected by AIT . The exception to this would be an increase in IL‐10‐expressing B cells, or Breg, which is associated with tolerance to bee venom and SLIT for grass pollen and HDM allergies …”
Section: Candidate Biomarkers For Immune Monitoring In Allergen Immunmentioning
confidence: 99%
“…33 The exception to this would be an increase in IL-10-expressing B cells, or Breg, which is associated with tolerance to bee venom and SLIT for grass pollen and HDM allergies. 36,128,129…”
Section: T Cellsmentioning
confidence: 99%
“…The understanding of the sequence of immunological events might be a prerequisite for the development of novel therapeutic strategies. Hence, in addition to the typical disease‐associated parameters, a special focus of this study was the effect of IL‐4/IL‐13 receptor inhibition on lung‐resident populations of Th2 and Treg cells at different time points of therapy, some of which are hypothesized to represent an intermediate cell population on the edge between allergen reactivity and tolerance loss …”
Section: Introductionmentioning
confidence: 99%